Pembatalan Akta Perjanjian Pinjam Meminjam dan Kuasa Menjual yang Dibuat Notaris Karena Alasan Adanya Cacat Kehendak: (Analisis Putusan Mahkamah Agung Nomor 2828 K/Pdt/2017) - Chrisintia Sitompul; Hasim Purba; Mahmul Siregar (Jurnal Hukum Lex Generalis, 2025)
An agreement arises from the mutual consent of two or more parties. This consent in formed through the meeting of an offer and an acceptance. For an agreement to be valid and binding, it must meet serveral conditions as sipulated in Article 1320 of the Indonesian Civil Code. However, it is posible for such consent to be flawed due to a defect of will (wilsgebreke). This research is a normative juridical study with a descriptive aproach. The case analyzed in Supreme Court Decision Number 2828 K/Pdt/2017 Concerns the nullification of notarial Deed Number 4 and Deed number 5 dated August 5,2015, wich where deemed legally invalid due to actions of one party and the involvement of the notary. This study found that the defect of will included deceit, fraud, and imbalance in the formation of the deed. The cancelation of a notarial deed nullifies its legal force, and thus renders the legal consequences of the agreement unenforceable.